Delineating the proof-of-concept of virtual reality for interprofessional education in simulating obesity case management - Mohd Yusof, Barakatun Nisak; Hashim, Norkamaliah; Hod, Rafidah; Jahn Kassim, Puteri Shanaz; Mat Daud, Zulfitri Azuan (Human Resource Management Academic Research Society, 2021)
This article delineates the proof-of-concept of virtual reality for interprofessional education in simulating obesity case management among healthcare profession students. Healthcare profession students, including dietetics, medical and nursing students in Universiti Putra Malaysia, will be recruited as a sample. This study starts with a workshop session on IP simulation-based obesity education and will be integrated into the virtual world (VW) online software. Students' knowledge and attitude will be assessed pre and post of the virtual IPE exposures. The developed obesity-simulated case would successfully lead to IPE implementation, and students who received virtual IPE would significantly have a better knowledge of obesity management and a positive attitude towards IPE. The virtual IPE would be a practical pedagogical approach to prepare the health profession students for a collaborative environment, improve technical skills, and strengthen soft skills such as communicating effectively.